A functional and semantic description of traditional measurement units in the English language - Boboyeva , Muazzam (The Lingua Spectrum, 2025)
This article provides a comprehensive study of the functional and semantic characteristics and meanings of traditional measurement units used in the English language. It focuses on traditional (non-standardized) measurement units that have been in use for centuries. The discussion centers on measurement units commonly used in the United States and the United Kingdom, as well as those recognized internationally. Today, all types of measurements are carried out using standardized units such as meters, grams, seconds, and so on (as established by the SI system). However, in the past, up until the end of the 20th century, these systems did not exist, and every nation relied on ancient, culturally rooted units such as spans, cubits, steps, handfuls, and others, based on their daily needs and tasks. The SI system enabled the standardization of measurement units on a global scale, which in turn contributed to the production of goods that meet uniform international standards and are competitive in the global market.